Interrater and intra-rater reliability of the VERA-2R tool - Duits, Nils; Kempes, Maaike (Frontiers in Psychiatry, 2023)
The Violent Extremism Risk Assessment -Version 2 Revised (VERA-2R) is an evidence-based structured professional judgement (SPJ) tool for ideologically motivated violence. Use of the tool can help professionals in risk assessment and risk management of suspected and convicted terrorists and violent extremists at different stages within the criminal process. It is important that the tool leads to reliable and valid risk assessments. Therefore, the present study aimed to establish the reliability of the VERA-2R, focusing on the interrater-and intrarater reliability. Trained researchers assessed the interrater-and intrarater reliability, respectively in 30 and 33 cases of Dutch convicted terrorist offenders, on the basis of extensive judicial files. In general, the average amount of agreement on the indicators and structured risk judgements can be classified as good to excellent, for both the interrater-and intra-rater reliability. However, six indicators were found to have low reliability. Above clarifying the reliability of the VERA-2R, this study also showed how the interrater-and intrarater reliability of a SPJ tool can be investigated with trained assessors based on judicial files. This can be of added value, because existing reliability studies often use case vignettes, have a small sample size and/or do not include a stringent training program. However, in order to develop a more reliable and valid VERA-2R tool, the remaining psychometric properties of the tool must also be investigated.